2017
DOI: 10.1080/10903127.2017.1335818
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Naloxone Redosing in the Age of the New Opioid Epidemic

Abstract: In this prehospital study, we confirmed that intranasal naloxone is effective in reversing suspected opioid toxicity. Nine percent of patients required two or more doses of naloxone to achieve clinical reversal of suspected opioid toxicity. Two percent of patients received a third dose of naloxone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Routine toxicological detection of FAs is difficult, and clandestine laboratories can easily modify fentanyl and its derivatives. Expanded access to addiction treatment and ready availability of naloxone to treat acute opioid overdoses are needed (Frank and Pollack, 2017;Klebacher et al, 2017;Samet and Kertesz, 2018;Thomson et al, 2017;CDC, 2018). Multifaceted fentanyl outbreak identification, prevention, harm reduction, and expanded treatment strategies that consider social, economic, and other contributing factors are needed to address the opioid and illicit drug crisis (Dasgupta et al, 2018;CDC, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Routine toxicological detection of FAs is difficult, and clandestine laboratories can easily modify fentanyl and its derivatives. Expanded access to addiction treatment and ready availability of naloxone to treat acute opioid overdoses are needed (Frank and Pollack, 2017;Klebacher et al, 2017;Samet and Kertesz, 2018;Thomson et al, 2017;CDC, 2018). Multifaceted fentanyl outbreak identification, prevention, harm reduction, and expanded treatment strategies that consider social, economic, and other contributing factors are needed to address the opioid and illicit drug crisis (Dasgupta et al, 2018;CDC, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 2166 patients treated by paramedics in New Jersey from 2014 to 2016 for a suspected opioid overdose, 91% experienced complete resolution of symptoms with a single dose of naloxone using an INND and 9% needed a second dose, generally by the intravenous route. 12 Training is needed to understand how to assemble and use the INND, and even with training, there is a 45% failure rate in its use by the public. 13 A portion of the naloxone solution delivered using the device may be lost dripping down the nasopharynx or externally from the nose because of the introduction of a 1-mL solution into each naris.…”
Section: Discussionmentioning
confidence: 99%
“…Of these events, 83% reported that 2 or more doses of naloxone using the INND per suspected fentanyl overdose were used before the person responded. In a retrospective study of 2166 patients treated by paramedics in New Jersey from 2014 to 2016 for a suspected opioid overdose, 91% experienced complete resolution of symptoms with a single dose of naloxone using an INND and 9% needed a second dose, generally by the intravenous route …”
Section: Discussionmentioning
confidence: 99%
“…Delivery of naloxone by the nasal route has been recognized by the medical community and public officials as an effective way to reverse opioid overdoses (Ryan and Dunne, 2018). However, the short half-life of naloxone and the increased incidence of overdoses linked to synthetic opioids with a longer duration of action may require more than one dose to be administered to prevent renarcotization (Klebacher et al, 2017). Therefore, the addition of a longer-acting opioid antagonist to the naloxone formulation was initially hypothesized as a means to increase the time to obtain proper medical attention.…”
Section: Discussionmentioning
confidence: 99%